Phenolic Profile and Antioxidant Capacity of Invasive Solidago canadensis L.: Potential Applications in Phytopharmacy - Mirela Uzelac Božac; Danijela Poljuha; Slavica Dudaš; Josipa Bilić; Ivana Šola; Maja Mikulič-Petkovšek; Barbara Sladonja (Plants)
Canadian goldenrod (Solidago canadensis L.), an invasive plant in Europe, is known for its allelopathic activity and is rich in bioactive compounds like flavonoids and phenolic acids, with significant pharmacological potential. This study presents the LC-MS phenolic profiles of leaf and flower extracts from S. canadensis, an invasive alien plant in the Istria region (Croatia). Total phenolics (TP) (45.78–110.68 mg GAE/g DW) and non-flavonoids (TNF) (28.38–72.20 mg GAE/g DW) were found to be more abundant in ethanolic than in methanolic extracts. The antioxidant capacity (AC), as measured by ABTS, DPPH, and FRAP assays, was higher in flower extracts compared to leaf extracts. A non-targeted metabolomics approach was used, and 41 phenolic compounds in leaves and 36 in flowers were identified, with hydroxycinnamic acids and flavonols being the most abundant. 5-caffeoylquinic acid was quantitatively predominant in the leaf extracts, while quercetin-3-rutinoside dominated the flower extracts. Five leaf-specific compounds were identified (dicaffeoylquinic acid 2, 4-p-coumaroylquinic acid 1, p-hydroxybenzoic acid, quercetin-3-rhamnoside, and quercetin acetylhexoside 1), suggesting targeted extraction for different pharmacological applications. This study highlights the therapeutic potential of S. canadensis and underscores the need for further research on the bioavailability, efficacy, and safety of its compounds, potentially transforming this ecological threat into a valuable resource for drug development.